Surveying the Field of Collective Memory Studies (KULT_online, 2010)
Cultural Memory Studies: An International and Interdisciplinary Handbook is a survey of the complex and disparate field of cultural/collective memory studies. The volume, edited by Astrid Erll and Ansgar Nünning, provides an account of research in this broad field that is at once systematic, historical, genealogical and disciplinary. Bringing together contributions from history, philosophy, literary studies, sociology, political science, media studies and psychology, the volume examines relationships between culture and memory, their individual and social aspects, mnemonic products, and processes of remembrance. The negotiation of interdisciplinary links makes this handbook a first step towards the development of a meta-concept of memory in sociocultural contexts.